Reducing Early Antibiotic Use: A Quality Improvement Initiative in a Level III Neonatal Intensive Care Unit - Morales-Betancourt, Catalina; De la Cruz-Bértolo, Javier; Muñoz-Amat, Bárbara; Bergón-Sendín, Elena; Pallás-Alonso, Carmen (Frontiers in Pediatrics, 2022)
Antibiotic burden is a critical issue in neonatal intensive care units (NICU) and antibiotic use is considered a quality indicator of neonatal care. Our aim was to optimize antibiotic use through a quality improvement (QI) initiative that included revision of departmental protocols and implementation of a surveillance system based on process indicators. Methods: This is descriptive study of a cohort of all very low birth weight (VLBW) infants admitted to the NICU from 2014 to 2019. A series of QI interventions were made during the study period and included departmental protocols and the implementation of a surveillance system based on process indicators. The primary outcome was the percentage of VLBW infants who had received early antibiotics (ampicillin, gentamycin, or cefotaxime on the day of birth or day 1 or 2 after birth), antibiotics for >3 days (despite negative blood culture), or no antibiotics. Results: During the study period, a significant relative reduction was seen in the proportion of VLBW infants administered early antibiotics (46%; p < 0.01) and in infants provided antibiotics for >3 days (90%; p < 0.01). Additionally, the percentage of VLBW with “no antibiotics” during their NICU stay increased fivefold (6% to 30%; p<0.001). Conclusions: In our NICU, the implementation of a QI initiative that is based on affordable methods to track process indicators and evaluate the results led into a significant reduction in antibiotic exposure in VLBW infants. This approach is easy to implement in other NICUs as well.